Low-cost hydrogen embrittlement-resistant titanium bipolar plate for electrolytic bath and preparation method thereof
By surface modification, heat treatment and coating of the titanium substrate of the PEM water electrolytic cell bipolar plate, the hydrogen embrittlement problem is solved, the hydrogen embrittlement resistance and conductive corrosion resistance are improved, and the manufacturing cost is reduced.
Patent Information
- Application Number
- CN202411961652.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-22
AI Technical Summary
The existing PEM water electrolytic cell bipolar plates are susceptible to hydrogen permeability in a high-purity hydrogen environment, resulting in hydrogen embrittlement problems, which in turn causes safety hazards and mechanical performance losses.
By roughening and modifying the surface of the titanium substrate, heat treatment is performed to generate a dense titanium oxide layer, and coating the surface of the noble metal conductive layer, forming a multi-protective structure that resists hydrogen embrittlement.
It significantly improves the hydrogen embrittlement resistance of the titanium bipolar plate, ensures conductivity and corrosion resistance, and reduces manufacturing costs.
Smart Images

Figure CN119859814A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bipolar plates for proton exchange membrane water electrolyzers, and in particular relates to a low-cost hydrogen embrittlement-resistant titanium bipolar plate for electrolyzers and a preparation method thereof. Background Art
[0002] Hydrogen is one of the most abundant elements in nature and plays an important role in energy and chemical industry, energy storage and power generation, food processing and other fields. Proton exchange membrane water electrolysis (PEM water electrolysis) is a green hydrogen production technology that has developed rapidly in recent years. It has a compact structure and can be effectively coupled with intermittent electricity generated by renewable energy (such as solar energy, wind energy, tidal energy, etc.). It has unparalleled advantages such as high current density, high purity of hydrogen production, and high electricity-to-hydrogen conversion efficiency.
[0003] Titanium is the preferred material for bipolar plates in PEM water electrolyzers due to its excellent corrosion resistance and high specific strength. The cathode side of the PEM water electrolyzer is where the hydrogen evolution reaction occurs. The sulfonic acid groups inside the proton exchange membrane can conduct protons, allowing the H generated by hydrolysis at the anode of the electrolyzer to + Under the action of potential difference, the electrons pass through the proton exchange membrane to the cathode and react with the electrons conducted by the external circuit at the cathode to precipitate hydrogen. Therefore, the cathode side of the PEM water electrolyzer is a high-purity hydrogen environment. The hydrogen atom has the smallest atomic radius, which makes it have a strong diffusion ability in metals. When the surface of the metal material cannot effectively inhibit the dissociation of hydrogen molecules into atomic hydrogen (hydrogen atoms H, hydrogen ions H) + / H-), hydrogen can easily penetrate into the metal material and dissolve in it. When the amount of hydrogen absorbed exceeds the limit solubility of the titanium substrate, the hydrogen atoms diffused into the titanium substrate will exist in the form of hydrides. Titanium hydride reduces the tensile strength, fatigue strength and fracture toughness of the titanium bipolar plate, thereby causing hydrogen embrittlement of the titanium substrate due to hydrogen absorption, which in turn causes great safety hazards during the service of the PEM water electrolyzer.
[0004] The titanium substrate precious metal coating conventionally used for bipolar plates of PEM water electrolyzers cannot effectively inhibit the dissociation of hydrogen adsorbed on the cathode, resulting in poor hydrogen embrittlement resistance and high susceptibility to hydrogen penetration. It is generally believed that when the solubility of hydrogen in titanium exceeds several hundred ppm, the mechanical properties of titanium such as toughness and plasticity will be significantly reduced, and there is a risk of cracking under stress conditions.
[0005] In order to take into account the high conductivity requirements of the bipolar plate for the special zero-gap structure of the PEM water electrolyzer, the surface of the titanium bipolar plate is usually coated with a precious metal coating with high chemical stability and good conductivity, such as Pt, Au, Ir, etc. However, the single precious metal coating has limited resistance to hydrogen embrittlement, and hydrogen atoms have a high diffusion coefficient in single metals. Hydrogen often penetrates the coating from the coating defects and invades the interior of the precious metal, causing hydrogen embrittlement. Usually, extremely low levels of hydrogen will cause serious damage to the mechanical properties of titanium materials. For example, when the hydrogen content in TC4 titanium alloy increases from 10ppm to 50ppm, its fracture toughness will decrease by 25% to 50%. Combined with the high assembly load of the PEM water electrolyzer, the loss of mechanical properties of the titanium bipolar plate means an increase in the safety risk of hydrogen production. Increasing the thickness of the precious metal coating can form a dense coverage of the precious metal coating, thereby alleviating the penetration of hydrogen, but this will lead to an increase in the overall manufacturing cost of the electrolyzer.
[0006] Patent document CN117568838A discloses a carbon-coated bipolar plate for a PEM electrolyzer and a preparation method thereof. The coating comprises a gradient metal-carbon transition layer and a pure carbon coating, and has multiple functions of being conductive, corrosion-resistant and hydrogen-embrittlement-resistant.
[0007] Patent document CN118773608A discloses a hydrogen embrittlement resistant composite coating for bipolar plates of PEM electrolyzers and a preparation method thereof. The coating comprises a hydrogen solidifying bottom layer, a hydrogen barrier layer and a conductive outer layer for inhibiting hydrogen dissociation, which are sequentially formed on the surface of the bipolar plate substrate of the PEM electrolyzer by physical vapor deposition. The material of the hydrogen solidifying bottom layer is selected from La, Ce, Ni, Co, Mn, Al metals and their alloys, zirconium-based alloys, titanium-based alloys, magnesium-based alloys and their oxides; the material of the hydrogen barrier layer is selected from W, Be, W-Be alloys, nitrides, carbides, oxides, and the hydrogen diffusion coefficient is less than 10 -14 mol / s / m / Pa 0.5, the conductive outer layer material for inhibiting hydrogen dissociation is selected from Ag, Au, Cu-Ag, Cu-Au materials, and the hydrogen dissociation energy is greater than 0.1eV. However, (1) the document adopts a coating combination of multiple different material systems to improve the hydrogen embrittlement resistance. The interface matching of different layers is difficult, the process complexity is high, and the processing cost is not advantageous. (2) The composite coated bipolar plate in the document includes a large amount of alloy substrate, metal and its alloy or metal compound coating (such as iron-based, chromium-based, nickel-based, magnesium-based, copper-based, etc.), which will lead to the precipitation of various types of ions under the harsh actual working conditions of proton exchange membrane water electrolysis, thereby poisoning the proton exchange membrane and causing the electrolysis efficiency to decrease. The site affinity of metal cations to sulfonic acid groups in proton exchange membranes is higher than that of protons, but their migration rate in proton exchange membranes is much lower than that of protons. Therefore, metal cations will occupy the proton transport channel, reduce the proton conductivity, and increase the ohmic loss of the membrane internal resistance. In addition, Ni ions have a more negative reversible potential relative to the cathode hydrogen evolution potential, and are prone to single-layer underpotential deposition on the cathode catalyst surface. The catalyst surface is covered, resulting in an increase in the cathode overpotential. Mg ions are prone to react with water molecules dragged from the anode to the cathode to form hydroxide precipitates, thereby covering the reaction active sites and reducing the catalytic reaction rate. Summary of the invention
[0008] The purpose of the present invention is to provide a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell and a preparation method thereof, which includes three main processes: surface modification of a titanium substrate, heat treatment, and coating of a conductive layer. The hydrogen embrittlement resistance of the titanium bipolar plate is significantly improved without sacrificing corrosion resistance and electrical conductivity.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] The low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell of the present invention comprises: a surface-modified titanium substrate, an in-situ hydrogen barrier layer formed on the surface of the titanium substrate, and a noble metal conductive layer prepared on the surface of the in-situ hydrogen barrier layer;
[0011] The surface roughness Ra value of the surface modified titanium substrate is 2 to 3.5 μm;
[0012] The in-situ hydrogen barrier layer is a titanium oxide layer or an oxygen inclusion layer in-situ generated on the surface of the titanium substrate in an atmospheric atmosphere or an oxygen-rich atmosphere, and has a thickness of 50 to 200 nm;
[0013] The material of the noble metal conductive layer is at least one of platinum, gold, iridium and palladium, and the thickness is 20 to 150 nm.
[0014] The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to the present invention comprises the following steps: performing three processes of surface roughening, heat treatment and conductive layer coating on a titanium substrate in sequence;
[0015] The surface roughening is: roughening the surface of the titanium substrate by at least one of sandblasting, laser irradiation, ion beam bombardment and / or acid chemical etching;
[0016] The heat treatment comprises: heat treating the surface-modified titanium substrate in an atmospheric atmosphere or an oxygen-rich atmosphere to form a dense titanium oxide layer or an oxygen inclusion layer on the surface of the titanium substrate;
[0017] The conductive layer coating is as follows: a layer of noble metal conductive layer is coated on the surface of the heat-treated titanium substrate.
[0018] Preferably, the titanium bipolar plate is one of a pure titanium flat plate formed by rolling or machining, a titanium flow field plate formed by stamping, and a titanium flow field plate with a chemically etched flow channel; the preferred thickness is 0.5 to 2 mm; the preferred titanium substrate is industrial pure titanium material labeled TA1 or TA2, with a low content of impurity elements, which can effectively avoid membrane electrode contamination problems caused by the precipitation of impurity elements.
[0019] Preferably, before the surface roughening, the titanium substrate should be pretreated: the titanium substrate is ultrasonically cleaned in acetone and ethanol respectively, and dried with cold air to remove grease, dust or other pollutants adhering to the surface.
[0020] The main purpose of the surface modification process is to make the surface of the titanium substrate uneven, increase the specific surface area and surface roughness, and then increase the local fluctuation of the electron work function. Therefore, the rough surface of the titanium substrate has a higher electrochemical activity than the flat surface, which can increase the proportion of hydrogen atoms adsorbed on the surface of the titanium substrate, thereby reducing the absolute flux of hydrogen atoms invading the substrate; microscopically, the substrate surface forms microstructures and high-density lattice defects (dislocations, vacancies, grain boundaries, etc.), and these microstructures and defects form high-density hydrogen capture sites, that is, "hydrogen traps". When the invading hydrogen atoms fill the hydrogen traps to saturation, the subsequent hydrogen atoms will diffuse in the substrate metal lattice. By increasing the density of microstructures and lattice defects, the diffusion rate and diffusion flux of hydrogen in the titanium bipolar plate substrate can be slowed down.
[0021] The purpose of the heat treatment step is to form a dense titanium oxide layer (TiO x ) or oxygen inclusion layer. It is generally believed that the hydrogen embrittlement sensitivity of compounds and alloys is much lower than that of single metals. The dense Ti-O layer generated in situ can effectively block the intrusion and penetration of hydrogen. Preferably, the heat treatment temperature is 400-550°C and the holding time is 1-3h.
[0022] Preferably, the heat treatment is carried out in a temperature-controllable box furnace or a muffle furnace.
[0023] The conductive layer coating process is to ensure the high conductivity and chemical stability of the titanium bipolar plate substrate and to isolate the direct contact between hydrogen and the titanium material. The conductive layer coating is carried out by at least one of physical vapor deposition, chemical vapor deposition, electroplating, chemical plating and / or thermal decomposition.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention roughens the surface of the titanium substrate to reduce the absolute flux of hydrogen atoms invading the substrate. The heat treatment process generates a hydrogen barrier layer in situ to block the diffusion of hydrogen into the interior of the substrate, thereby achieving multiple protections for the titanium bipolar plate together with the precious metal conductive layer in a high-purity hydrogen environment, greatly improving the hydrogen embrittlement resistance of the titanium bipolar plate, and ensuring that the titanium bipolar plate has both anode conductivity and corrosion resistance and cathode hydrogen embrittlement resistance, without increasing the thickness of the outer conductive layer to block the invasion of hydrogen. The use of a low-load precious metal conductive layer also greatly reduces the overall manufacturing cost.
[0026] The present invention has high process maturity, low process complexity, low material cost and great cost advantage through simple surface modification and in-situ generation of a hydrogen barrier layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the structure of the hydrogen embrittlement resistant titanium bipolar plate of the present invention.
[0028] Figure 2 Schematic diagram of the surface roughening modification of titanium bipolar plates to delay hydrogen embrittlement.
[0029] Figure 3 XRD spectra of the titanium bipolar plates of Example 1 and Comparative Example 1 after being tested for 800 hours.
[0030] Figure 4 XRD spectra of the titanium bipolar plates of Example 2 and Comparative Example 2 after 800 hours of testing. DETAILED DESCRIPTION
[0031] Those skilled in the art should recognize that the present embodiment is only used to illustrate the present invention, and is not used to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.
[0032] Example 1
[0033] A low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell uses a TA1 chemically etched pure titanium flow field plate with a thickness of 2 mm and good uniformity as a titanium substrate, and the preparation method is as follows:
[0034] (1) The titanium substrate was ultrasonically cleaned in acetone and ethanol for 15 min each to remove grease, dust or other contaminants adhering to the surface.
[0035] (2) The pre-treated titanium substrate was sandblasted with 60# white corundum at a sandblasting angle of 45° to 55°, a sandblasting distance of 100 to 150 mm, and a gas pressure of 0.5 MPa, so that the surface of the titanium substrate formed a rough surface with a roughness Ra value of 3 to 3.5 μm. The titanium substrate after sandblasting was repeatedly rinsed with deionized water for 10 minutes and dried under hot air at 100°C.
[0036] (3) The surface-roughened titanium substrate is placed in a muffle furnace and heated to 550° C. in an oxygen-rich atmosphere for 1 hour, so that a dense titanium oxide layer (in-situ hydrogen barrier layer) is in situ generated on its surface with a thickness of about 150 nm.
[0037] (4) Use a soft brush to evenly apply the platinum coating liquid on the surface of the titanium oxide layer of the titanium substrate, dry it at 120°C for 10 minutes, and then move it to an oxidation furnace and oxidize it at 450°C for 30 minutes. The platinum coating liquid is a 10g / L chloroplatinic acid n-butanol solution; the atmosphere of the oxidation furnace is air containing about 5% argon by volume; hang it to cool naturally, and then repeat the above-mentioned brushing, drying, oxidation, and cooling operations twice; the thickness of the obtained platinum precious metal conductive layer is about 150nm.
[0038] Comparative Example 1
[0039] Comparative Example 1 is a comparative example of Example 1.
[0040] In Comparative Example 1, the surface of the titanium substrate was not roughened or heat treated, and only the precious metal coating was applied. The specific steps are as follows:
[0041] (1) A TA1 chemically etched pure titanium flow field plate with a thickness of 2 mm and good uniformity was used as the titanium substrate, and ultrasonically cleaned in acetone and ethanol for 15 min each to remove grease, dust or other contaminants adhering to the surface.
[0042] (2) Use a soft brush to evenly apply the platinum coating liquid on the surface of the titanium substrate, dry it at 120°C for 10 minutes, and then move it to an oxidation furnace and oxidize it at 450°C for 30 minutes. The platinum coating liquid is a 10g / L chloroplatinic acid n-butanol solution; the atmosphere of the oxidation furnace is air containing about 5% argon by volume; hang it for natural cooling, and then repeat the above-mentioned brushing, drying, oxidation, and cooling operations 5 times; the thickness of the obtained platinum precious metal conductive layer is about 300nm.
[0043] Example 2
[0044] A low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell uses a TA2 pure titanium flat plate with a thickness of 0.8 mm and good uniformity as a titanium substrate, and the preparation method is as follows:
[0045] (1) The titanium substrate was ultrasonically cleaned in acetone and ethanol for 15 min each to remove grease, dust or other contaminants adhering to the surface.
[0046] (2) The titanium substrate was immersed in a 10% oxalic acid solution, kept warm for 2 hours under boiling conditions, taken out, rinsed with deionized water for 10 minutes, and dried under hot air at 100°C to form a rough surface with a roughness Ra value of 2 to 2.5 μm on the titanium substrate. The titanium substrate was repeatedly rinsed with deionized water for 10 minutes and dried under hot air at 100°C.
[0047] (3) The surface-roughened titanium substrate is placed in a muffle furnace and heated to 450° C. in an air atmosphere for 2 h, so that a dense oxygen inclusion layer (in-situ hydrogen barrier layer) is in situ generated on its surface with a thickness of about 100 nm.
[0048] (4) Using DC magnetron sputtering technology, a platinum coating is deposited on the surface of the oxygen inclusion layer of the titanium substrate. When the background vacuum of the vacuum chamber reaches 1×10 -3 High-purity argon gas was introduced at 0.5 Pa, and the coating was deposited when the chamber pressure was stabilized at about 0.5 Pa. The deposition current was 1.2 A, the deposition temperature was 250 ° C, the substrate bias was set to -200 V, the deposition time was 10 min, and the deposited coating thickness was about 100 nm.
[0049] Comparative Example 2
[0050] Comparative Example 2 is a comparative example of Example 2.
[0051] In Comparative Example 2, the surface of the titanium substrate was not roughened or heat treated, but only the precious metal coating was applied. The specific steps are as follows:
[0052] (1) A TA2 pure titanium plate with a thickness of 0.8 mm and good uniformity was used as the titanium substrate, and ultrasonic cleaning was performed in acetone and ethanol for 15 min each to remove grease, dust or other contaminants adhering to the surface.
[0053] (2) Using DC magnetron sputtering technology, a platinum coating is deposited on the surface of the titanium substrate. When the background vacuum of the vacuum chamber reaches 1×10 -3 High-purity argon gas was introduced at 0.5 Pa, and the coating was deposited when the chamber pressure stabilized at about 0.5 Pa. The deposition current was 1.2 A, the deposition temperature was 250 ° C, the substrate bias was set to -200 V, the deposition time was 20 min, and the deposited coating thickness was about 200 nm.
[0054] The corrosion test includes a potentiodynamic polarization test (Tafel extrapolation method to determine the corrosion current density) and a 1.6V constant potential polarization test (to determine the contact resistance of the sample before and after corrosion); the corrosion solution is 0.5MH2SO4+0.1ppm HF, the holding time is 80℃, and the 1.6V constant potential polarization test duration is 24h. According to GB / T 20042.6-2011 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method", the contact resistance with carbon paper is tested under a pressure of 2.4MPa. The coating adhesion is tested according to the GB / T 9286-2021 Hundred Grid Method, and the test results are shown in Table 1.
[0055] Table 1 Test results of Examples 1 to 2 and Comparative Examples 1 to 2
[0056]
[0057] It can be seen from Table 1 that the anti-hydrogen embrittlement coating of the present invention has the same conductive and corrosion-resistant properties as the pure precious metal coating, and the film-base interface is matched and the coating is well bonded.
[0058] The titanium-based bipolar plates of Examples 1-2 and Comparative Examples 1-2 were assembled into different sections of the same PEM electrolyzer. Other materials such as membrane electrode, cathode and anode diffusion layer, sealing materials, etc. were all produced in the same batch and of the same model. 2 The durability test was conducted for 800 hours at a constant current density. After the durability test, the cathode reaction area of the titanium bipolar plate was sampled for XRD test. The results are shown in Figure 3 and Figure 4 It can be clearly seen that the titanium bipolar plates of Examples 1 to 2 have almost no hydride generated on the surface under the long-term service environment of the electrolytic cell, and have excellent hydrogen embrittlement resistance.
Claims
1. A low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell, characterized in that: The method comprises: a surface-modified titanium substrate, an in-situ hydrogen barrier layer formed on the surface of the titanium substrate, and a noble metal conductive layer prepared on the surface of the in-situ hydrogen barrier layer; The surface roughness Ra value of the surface modified titanium substrate is 2 to 3.5 μm; The in-situ hydrogen barrier layer is a titanium oxide layer or an oxygen inclusion layer in-situ generated on the surface of the titanium substrate in an atmospheric atmosphere or an oxygen-rich atmosphere, and has a thickness of 50 to 200 nm; The material of the noble metal conductive layer is at least one of platinum, gold, iridium and palladium, and the thickness is 20 to 150 nm.
2. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 1, characterized in that: The method comprises the following steps: performing three processes of surface roughening, heat treatment and conductive layer coating on the titanium substrate in sequence; The surface roughening is: roughening the surface of the titanium substrate by at least one of sandblasting, laser irradiation, ion beam bombardment and / or acid chemical etching; The heat treatment comprises: heat treating the surface-modified titanium substrate in an atmospheric atmosphere or an oxygen-rich atmosphere to form a dense titanium oxide layer or an oxygen inclusion layer on the surface of the titanium substrate; The conductive layer coating is as follows: a layer of noble metal conductive layer is coated on the surface of the heat-treated titanium substrate.
3. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 2, characterized in that: The titanium bipolar plate is one of a pure titanium flat plate formed by rolling or machining, a titanium flow field plate formed by stamping, and a titanium flow field plate with a chemically etched flow channel.
4. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 2, characterized in that: The thickness of the titanium bipolar plate is 0.5-2 mm; the titanium substrate is made of industrial pure titanium with the label TA1 or TA2.
5. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 2, characterized in that: Before the surface roughening, the titanium substrate should be pretreated: the titanium substrate is ultrasonically cleaned in acetone and ethanol respectively, and dried with cold air.
6. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 2, characterized in that: The heat treatment temperature is 400-550°C and the holding time is 1-3h.
7. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 2, characterized in that: The heat treatment is carried out in a temperature-controllable box furnace or a muffle furnace.
8. The method for preparing a low-cost hydrogen embrittlement-resistant titanium bipolar plate for an electrolytic cell according to claim 2, characterized in that: The conductive layer is coated by at least one of physical vapor deposition, chemical vapor deposition, electroplating, chemical plating and / or thermal decomposition.
Citation Information
Patent Citations
PEM electrolytic cell bipolar plate and preparation method thereof
CN117568838A
Hydrogen embrittlement resistant composite coating for bipolar plate of PEM electrolytic cell and preparation method thereof
CN118773608A
Cited By
Preparation method of titanium-based water electrolysis hydrogen production electrode and titanium-based water electrolysis hydrogen production electrode
CN121737798A
High-pressure-resistant hydrogen-embrittlement-resistant metal rubber composite sealing material and preparation method thereof
CN121871208A
High-pressure-resistant hydrogen embrittlement-resistant metal-rubber composite sealing material and preparation method thereof
CN121871208B